Expression of Phosphorylated Signal Transducer and Activator of Transcription 3 and its Prognostic Significance in Canine Anal Sac Adenocarcinoma. (January 2021) - Mosca, Andrea; Restif, Olivier; Dobson, Jane; Hughes, Katherine
Summary: Prognostication in canine anal sac adenocarcinomas (ASACs) is difficult due to conflicting evidence regarding metastatic rates and median survival times (MSTs). The transcription factor signal transducer and activator of transcription 3 (STAT3) is a prognostic predictor in several human cancers. The aim of this retrospective study was to assess STAT3 expression in ASACs and to explore its association with clinical presentation and outcome. We hypothesized that STAT3 expression would distinguish tumours with early versus late metastasis. Records from The Queen's Veterinary School Hospital, Cambridge, UK, were searched for dogs diagnosed with ASAC from 2008 to 2019. Immunohistochemical expression of phosphorylated STAT3 (pSTAT3) was assessed in primary tumours (n = 57) and metastatic lymph nodes (n = 30) and MSTs were calculated for cases with low and high pSTAT3 expression. Of the 57 cases assessed, 27 presented with primary tumours but no metastasis and 30 with both primary and local metastatic disease. Most cases (50/57) expressed nuclear pSTAT3 within neoplastic cells in both primary tumour and metastatic lymph nodes. pSTAT3 expression was predominantly observed in neoplastic cells at the edges of neoplastic lobules, suggesting a potential role in invasion. There was no significant difference in pSTAT3 expression between cases metastatic at presentation and those that did not have detectable metastasis at presentation. There was no significant difference between the MSTs in cases with high and low pSTAT3 expression. Cases that presented with metastatic disease had shorter MSTs (395 days) than those with primary tumours alone (623 days). Although pSTAT3 is variably expressed in primary and metastatic ASAC cells, pSTAT3 did not provide prognostic information for canine ASAC.